Which model to forecast the target rate? - Bruno Feunou; Jean-Sébastien Fontaine; Jianjian Jin (Bank of Canada, 2017)
Specifications of the Federal Reserve target rate that have more realistic features mitigate in-sample over-fitting and are favored in the data. Imposing a positivity constraint and discrete increments significantly increases the accuracy of model out-of-sample forecasts for the level and volatility of the Federal Reserve target rates. In addition, imposing the constraints produces different estimates of the response coefficients. In particular, a new and simple specification, where the target rate is the maximum between zero and the prediction of an ordered-choice Probit model, is more accurate and has higher response coefficients to information about inflation and unemployment.
Keywords: E43; 330; Financial markets; Interest rates